Gestão financeira das pequenas e médias empresas da indústria da construção civil do estado de Sergipe : uma análise sob a ótica da liquidez - Carvalho Filho, Paulo Freire (2011)
This dissertation examines the liquidity situation of small and medium enterprises of construction segment, acting in Sergipe s public construction market. To achieve the objectives of this study we used the methods i) traditional and ii) dynamic (Fleuriet Model), because they have different methodologies of analysis, noting that the first through the CCL, ILC and ILG indicators, shows the liquidity situation at a given instant of time, as the timely indicator of solvency, while the second, using the CDG, NCG, T, AE, ILNCG and ILAE indicators, clarifies the need for working capital for the operating activities of the company, essential to the sustainability and business growth. Following the assumption of the dynamic model, the accounts of Balanços Patrimoniais and Demonstrações do Resultado do Exercício for the years 2007, 2008 and 2009 were reclassified. For this case study, 20 companies registered with the Companhia Estadual de Habitação e Obras Públicas CEHOP were selected, with contracts in force for the period 2007 to 2009, with 14 classified as medium and 6 as small businesses, using the Lei Complementar (Federal) Nº 123/2006 criterion. Through this research, it was sought to identify the financial management from the perspective of liquidity of these small and medium enterprises, and the consequences of the application, by the State Government, of the prerogative to promote specific biddings to small businesses provided in Lei Complementar (Federal) nº 123 / 2006 and Lei Estadual nº 6.206/2007. Considering the analysis of data as a group through the medians, the results indicate i) the framework for medium-sized enterprises in the type II (solid) NCG Dynamic Model in all exercises, and small type II in the years 2008 and 2009, and type I (excellent liquidity) in 2007, ii) the framework for medium-sized enterprises in the type D (financial strength) of the AE Dynamic Model in all exercises, and small in the type D (financial strength) in the years 2008 and 2009, and G (financial strength) in 2007; iii) an indication of liquidity in the financial medium and small companies when used indicators ILNCG, ILAE, ILC and ILG; iv) improved financial performance of small companies when compared from the standpoint of liquidity with the medium size; v) none of the two studied categories of companies (small and medium size) pointed to the occurrence of the "Efeito Tesoura" under Dynamic Analysis Model of both the NCG and AE; vi) indication of self-financing capacity of the operational activities of medium and small businesses; vii) there were no differences in results among the traditional indicators and the ones proposed by the dynamic models (within the limits of this case study); viii) small companies have treasury balances that support positive changes in the working capital needs caused by the leverage of their business. In the end, these results suggest applicability of the items I and II of article 48 of Lei Complementar (Federal) nº 123/2006 and items I and II of article 4 of Lei nº 6.206/2007 of Sergipe State, to do exclusive biddings for small business or their subcontracting in the other biddings, as public policy for promoting economic growth, employment and income. However, this observation from the analysis of accounting data of only 20 construction companies, selected by criteria of accessibility without statistical rigor, indicates the need to expand this research with a larger number of companies, to ensure the expected results in the adoption of this proposed public policy.